PENGARUH KOMPETENSI DAN DISIPLIN KERJA TERHADAP KINERJA PEGAWAI TIDAK TETAP PADA PUSKESMAS RAKADUA DI KECAMATAN POLEANG BARAT KABUPATEN BOMBANA - Alqadry, Defry; Hatani, La; Maharani, Sri Wiyati; Hastuti, Hastuti; Adam, La Ode Bahana (Jurusan Manajemen, Fakultas Ekonomi dan Bisnis Universitas Halu Oleo, 2023)
This study aims to: 1) Determine the effect of competence and work discipline simultaneously on the performance of non-permanent employees; 2) Knowing the effect of competence on the performance of non-permanent employees; 3) Knowing the effect of work discipline on the performance of non-permanent employees.The population in this study is all non-permanent employee performance Rakadua Health Center in Poleang Barat District, Bombana Regency, totaling 33 people and all populations are used as respondents. Data collection uses a questionnaire Theanalysisusedisquantitativeanalysisusing MultipleLinearRegressionAnalysis.The results of the study show that: 1) Competence and work discipline simultaneously have a positive and significant effect on non-permanent employees, 2) Competence partiallyhas a positive and significant effect on non-permanent employees. 3) Work discipline partially has apositive and significant effect on the performance of non-permanent employees at the RakaduaHealth Center in Poleang Barat District, Bombana Regency.